Silver Nanoparticles from Hermetia illucens Biomass Are Antibacterial Against Pseudomonas aeruginosa Infection in Caenorhabditis elegans - Alinne Ayech; Gabriela Hollmann; Robson M. Marreiro Gomes; Belisa A. Rodrigues; Vanessa K. Engers; Rafael S. Gonçalves; Sandro Daniel Nornberg; Daniela F. Ramos; Karine Rigon Zimmer; José M. Monserrat (Microorganisms, 2025)
Silver nanoparticles (AgNPs) are known for their antimicrobial properties, and can be synthesized through various routes. We used both chemical synthesis and green synthesis from the biomass of black soldier larvae (Hermetia illucens). To test the antimicrobial potential of these nanoparticles, we employed an in vitro test, with CFU counting, and also used the worm Caenorhabditis elegans as an in vivo model. C. elegans were infected with Pseudomonas aeruginosa and treated with AgNPs from both syntheses. These AgNPs exhibited absorption spectrum peaks around 400 nm and sizes of 8 ± 3.5 (chemical) and 11 ± 4.7 nm (green). P. aeruginosa-infected worms, without treatment with AgNPs, achieved 100% mortality within 3 days, while AgNPs-treated worms survived until the end of the experiment, with no statistical differences compared to the non-infected worms of the control group. The results demonstrate that nanoparticles produced from H. illucens biomass have antimicrobial capacity, reducing bacterial growth in vitro and being able to protect C. elegans from infection by P. aeruginosa, similar to those produced by chemical synthesis. However, AgNPs from green synthesis are less harmful to the environment while maintaining their antimicrobial potential.